Educação especial inclusiva e tecnologia social - Lopes, Valéria Rosa Farto; Freitas, Carlos Cesar Garcia; Freitas, Flaviane Pelloso Molina [UNESP] (My University, 2017)
This article presents an analysis of 34 Social Technology (TS) projects involving the special education theme, in order to verify TS 's contribution to it. For that, a descriptive research was carried out, with a quantitative approach, through documentary analysis. Among the results obtained, the main problems are related to low self-esteem and exclusion of people with disabilities; Among the strategies used the one of greater frequency was the one of professional qualification; The main responsible and partners in the projects were public schools and universities; Various types of disability are seen as: visual, physical, auditory, intellectual and multiple.
Inclusive special education and social technology
Keywords: Accessibility; Assistive Technology; Disabled person; Inclusion